ISLAMOPHOBIA: ANCAMAN MULTIKULTURALISME DI INDONESIA - Abdillah, Abdillah; Putri, Suci Triana (JPP (Jurnal Politik Profetik), 2022)
This article discusses islamophobia as a threat to multiculturalism in Indonesia. To test this assumption, this article uses the theory expressed by Huntington as a multicultural clash between Western civilization and Islam. The method used is qualitative-explorative with a phenomenological approach. By analysis using Nvivo 12 Pro Tools. The results of this study state that islamophobia has significantly undermined the harmonization of diversity in Indonesia. This is evidenced by the phenomenon of mutual disbelief among fellow Muslims and bigotry between Islamic groups in Indonesia. As an offer to face the threat of division from the high influence of islamophobia, it is to present Islam as rahmatan lil alamin to maintain national and state harmonization in Indonesia.